Effects of dark septate endophytic fungi on the performance of non-mycorrhizal cabbage plants under normal and low water conditions - Lukács, Alena F.; Herczeg, Gábor; Kovács, Gábor M. (Frontiers in Microbiology, 2025)
Drought, a major consequence of global environmental change, poses a serious threat to both natural and agricultural ecosystems. Root-associated fungi, particularly the widely distributed dark septate endophytes (DSE), are key components of the plant microbiome and can influence host plant performance in various ways. We conducted two manipulative experiments using two model DSE species from a semiarid habitat to investigate their effects on a non-mycorrhizal host plant (cabbage) under both normal and reduced water supply conditions. The positive effects of Periconia were limited—it not only increased root biomass but also reduced water potential and soil moisture under normal watering conditions. In contrast, Cadophora significantly increased shoot biomass (by up to 50%) and root biomass in one experiment. However, this was also associated with a decline in plant water potential, particularly at the cost of reduced plant water status, and their effects varied on the same host. Interestingly, autoclaved inoculum, also had positive effects on plant growth. Our findings highlight the potential role of symbiotic DSE fungi in mitigating drought stress and suggest their promise as biotechnological tools for addressing the increasing challenges posed by drought.